(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The 1:10,000 scale mapping of the southern part of the Aggtelek Plateau (Western Carpathians, Silica Nappe, NE Hungary) and the study of five sections revealed two Middle Triassic reef bodies. In the late Pelsonian the uniform Steinalm Platform was drowned and dissected due to the Reifling Event. A connection with the open sea was established, indicated by the appearance of gladigondolellid conodonts from the early Illyrian. Basins and highs were formed. In the NW part of the studied area lower - middle? Illyrian basinal carbonates were followed by a platform margin reef (early?-middle Illyrian; reef stage 1) developed on a morphological high. This is the oldest known Triassic platform margin reef within the Alpine-Carpathian region. The reef association is dominated by sphinctozoans and microproblematics. The fossils are characteristic of the Wetterstein-type reef communities. Differently from this in the SE part of the studied region a basin existed from the late Pelsonian until the early Ladinian. During the late Illyrian- early Ladinian, the reef prograded to the SE, and reef stage 2 was established. Meanwhile, on the NW part of the platform a lagoon was formed behind the reef. Based on our palaeontological study the stratigraphic range of Colospongia catenulata, Follicatena cautica, Solenolmia manon manon, Vesicocaulis oenipontanus must be extended down to the middle Illyrian. Synsedimentary tectonics were detected in the 1. Binodosus Subzone, 2. Trinodosus Zone - the most part of the Reitzi Zone, 3. Avisianum Subzone.